Minimising the loss of biodiversity and ecosystem services in an intact landscape under risk of rapid agricultural development - Williams, Brooke A.; Grantham, Hedley S.; Watson, James E.M.; Álvarez, Silvia J.; Simmonds, Jeremy S.; Rogéliz, Carlos A.; Silva, Mayesse Aparecida da; Forero-Medina, Germán; Etter, Andrés; Nogales, Jonathan; Walschburger, Tomas; Hyman, Glenn G.; et al. (IOP Publishing, 2020)
As humanity's demand for resources continues to rise and productive arable lands become increasingly scarce, many of Earth's remaining intact regions are at heightened risk of destruction from agricultural development. In situations where agricultural expansion is inevitable, it is important to manage intact landscape transformation so that impacts on environmental values are minimised. Here, we present a novel, spatially explicit, land use planning framework that addresses the decision making needed to account for different, competing economic-environment objectives (agricultural production value, biodiversity conservation, ecosystem service retention) when land use change is inevitable within an intact landscape. We apply our framework to the globally significant savannahs of the Orinoquia (Colombia), which in a post-conflict era is under increased agricultural development pressure. We show that while negative environmental impacts can be reduced through planning, the total area of land converted to agriculture is the unavoidable principal driver of biodiversity and ecosystem service loss. We therefore identify planning solutions that perform well across all objectives simultaneously, despite trade-offs among them. When 15%, 20%, 30% and 40% of the study area is allowed to be converted to agriculture, on average planning can improve species persistence and ecosystem service retention by up to 16%, 15%, 12%, and 9%, respectively, when compared to agricultural-focused solutions. Development in the region so far has had an unnecessarily large impact on environmental objectives due to a lack of effective land use planning, creating an 'opportunity debt'. Our study provides an evidence base to inform proactive planning and the development of environmentally sensible agricultural development policy and practice in the region. This framework can be used by stakeholders to achieve agriculture expansion goals and maximise economic profit while minimising impacts on the environment in the Orinoquia, or any relatively intact region that is being developed.